Crescimento, desenvolvimento e produtividade de canola em solo com excesso hídrico natural - Rocha, Leidiana da (2018)
This work aimed to evaluate the growth, development and productivity of canola genotypes grown in soil that presents poor natural drainage. The study was carried out in the years 2016 and 2017 in the farming field at the Federal University of Santa Maria, Santa Maria, RS, Brazil. A random block design was used, with plots subdivided in factorial scheme 2 x 4, being the factors, soil drainage (with and without use of drains) and canola hybrids (Hyola 433, Hyola 76, Alht B4 and Diamond), with four replications. It was assessed the height, number of leaves and leaf area of plants, sub-periods and total crop cycle, stomatal conductance, leaf photosynthetic rate, yield components, productivity, and grain oil and protein content. Soil water surplus causes reduction of plant population, height, leaf area and dry mass of shoots and roots of canola. The use of drains decreases adverse effects of water surplus, allowing a better establishment, growth and development of plants. The higher water surplus resulted from the absence of drains, affects negatively the development of canola, increasing the thermal time needed to complete the S-E, and E-IF sub-periods and shortening the grain filling sub-period. The most affected yield components by water surplus due to the absence of drains are the number of siliques per plant and the dry mass of the siliques, but the most determinant variable of grain productivity is the number of grains per silique. The low availability of solar radiation at the end of the reproductive phase slows the maturation of grain and extends this sub-period. Reducing the water surplus by the use of drains decreases its adverse effects on the plant photosynthetic rate and stomatal conductance and grain productivity of canola. The “Diamond” hybrid can be considered a promising genetic material to be grown in areas with water surplus, since surface drains are used.